The Effect of Conventional and Sonochemical Synthesis Methods on Gd2O3 Nanoparticles Properties - Muflikhah Muflikhah; W. Z. Lubis; R. P. Caesariyanti; Mujamilah Mujamilah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2022)
Paramagnetic Gd2O3 nanoparticles have been widely used as a contrast agent in bioimaging such as Magnetic Resonance Imaging (MRI). In this study, Gd2O3 nanoparticles were prepared using conventional and sonochemically precipitation methods, without any stabilizers. Gadolinium nitrate was used as a precursor and ammonium hydroxide as precipitating agent. The synthesized Gd2O3 nanoparticles were characterized using X-Ray Diffractometer (XRD), Particle Size Analyzer (PSA), Scanning Electron Microscope (SEM), and Vibrating Sample Magnetometer (VSM). It was found that Gd2O3 nanoparticles obtained in both methods have a cubic phase. The saturation magnetization (Ms) values of conventional and sonochemical samples were 1.63 emu/g and 1.44 emu/g respectively. The morphology of both samples shows agglomerated spherical shape in the nanometer range. The nanoparticles size of Gd2O3 that was confirmed by the Dynamic Light Scattering technique show samples from the sonochemical method has narrower size distribution (higher homogeneity) compare to samples from the conventional method. It was also found that the sonochemical synthesis technique is faster (time-saving), simple, convenient, and environmentally benign.